The Treasury Of David - "Spurgeon, C. H. (Charles Haddon), 1834-1892." ("Peabody, Mass. : Hendrickson Publishers :")
"Reprint. Originally published: 7 vols. London : Passmore and Alabaster, 1869-1885. Includes indexes. v. 1. Psalm I to LVII -- v. 2. Psalm LVIII to CX -- v. 3. Psalm CXI to CL. HIC.BIBLE"
Keywords: BIBLE. O.T. PSALMS -- COMMENTARIES.;BIBLE. O.T. PSALMS -- HOMILETICAL USE